Competition between thermodynamics, kinetics and growth mode in the early-stage oxidation of an equimolar CoCrFeNi alloy. (1st September 2020) - Yu, Xiao-Xiang; Taylor, Matthew A.; Perepezko, John H.; Marks, Laurence D.
Abstract: We demonstrate that the early-stage oxidation of a CoCrFeNi multi-principal element alloy depends upon a competition between kinetic and thermodynamic factors involving the relative diffusion rate of cations and oxygen, and how this couples to inward or outward oxide growth. The microstructures of oxide layers formed at temperatures from 500 to 800 °C for 0.5 h, as well as their chemical compositions, were investigated by transmission electron microscopy. A triple layer microstructure with an outer Fe-rich spinel oxide, an intermediate Cr-rich corundum structure, and a Ni-rich (Fe, Co, and Cr depleted) dealloyed region at the metal/oxide interface was observed. The dominant oxygen transport in corundum at 800 °C and below led to an inward growth of the corundum phase; the spinel oxide growth was dominated by cation diffusion, so it grew outward. The chromium was sequestered in the corundum layer, thereby favoring the formation of the chromium-free, Fe-rich spinel oxides with Co and Ni dopants. Since nickel cannot readily diffuse through corundum, it tends to remain in the alloy phase leading to the Ni-rich dealloyed region at the metal/oxide interface. Beyond the microstructure results, we exploit secondary electron image contrast to show the doping nature of the oxides, a p-type spinel and a n-type corundum growing on the metal surface. Graphical abstract: Image, graphical abstract